Kalapodi, Griechenland - Niemeier, Wolf-Dietrich (e-Forschungsberichte des DAI, 2023)
Excavations at the sanctuary of Apollon at Abai near Kalapodi were continued in two areas: beneath the cella of the Archaic South Temple and in the Classical bronze foundry to the west of the Archaic South Temple. The excavations in the former area were brought to an end by reaching the natural soil. A further temple could be identified, so that the temples have to be renumbered. Now there is a sequence – unique in Greece – of ten South Tempels comprising a time span from the Mycenaean period (15th century BC) to the Roman Imperial Period (2nd century AD). A new discovery, among others, was an oriental import, a bronze tongue phiale was found (figs. 3‒4). For erecting South Temple II the foundations of South Temple I (LH IIIA 1-LH IIIA 2, 2nd half of 15th to end of 14th century BC) were reused. In South Temple I, predecessors of the installations of South Temple II came to light. To the west of the Archaic South Temple the excavation of the foundry pit for casting statues was completed (fig. 12). It contained the remnants of two foundry proceedings (Fig. 13). Fragments of roof tiles of the first Classical North Temple, wich was destroyed by an earthquake in the winter of 426/25 BC, provide a terminus post quem. To the west and to the south of this foundry pit two more foundry pits are emerging.